2011
DOI: 10.1037/a0022763
|View full text |Cite
|
Sign up to set email alerts
|

Task-irrelevant angry faces capture attention in visual search while modulated by resources.

Abstract: We investigated the attentional capture effect of emotional faces under sufficient or restricted attentional conditions. In a modified visual search paradigm, three kinds of schematic faces (angry, happy, and neutral) served as stimuli. Participants were instructed to search for a target face indicated by a dot and to respond to the dot's position. In this design, the emotional content of the face is task-irrelevant and does not need to be attended. The results of Experiment 1 demonstrate that having an angry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 41 publications
5
36
0
1
Order By: Relevance
“…Studies have shown that more resources are needed to process sad faces (Srivastava & Srinivasan, 2010). In addition, negative faces tend to capture attention when multiple stimuli were presented in the display (Huang, Chang, & Chen, 2011;Öhman, Flykt, & Esteves, 2001; see Srinivasan & Gupta, 2010;Experiment 2). In our study, sad faces trying to capture attention might have to be strongly inhibited so that performance in the primary task was not affected, leading to negative evaluation in the high-load condition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that more resources are needed to process sad faces (Srivastava & Srinivasan, 2010). In addition, negative faces tend to capture attention when multiple stimuli were presented in the display (Huang, Chang, & Chen, 2011;Öhman, Flykt, & Esteves, 2001; see Srinivasan & Gupta, 2010;Experiment 2). In our study, sad faces trying to capture attention might have to be strongly inhibited so that performance in the primary task was not affected, leading to negative evaluation in the high-load condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the negativity bias are conditioned by a sort of “experimental negativity bias”: Whereas all studies present negative distractors, only 23 studies (41.82 %) present positive distractors too. Among the latter studies, which are especially relevant here since they allow valence effects to be distinguished from arousal effects, negative distractors, and not positive ones, elicited higher indices of attentional capture than did neutral distractors in 6 studies (Horstmann et al, 2006; Huang, Chang & Chen, 2011; Lichtenstein-Vidne et al, 2012; McSorley & van Reekum, 2013; Nummenmaa, Hyona & Calvo, 2009; Sussman, Heller, Miller & Mohanty, 2013) and, along with positive distractors, in 13 (Carretié et al, 2004; Carretié, Kessel, et al, 2013; Carretié, Rios, Periáñez, Kessel, & Álvarez-Linera, 2012; De Cesarei, Codispoti & Schupp, 2009; Fenske & Eastwood, 2003; Gilboa-Schechtman et al, 1999; Hahn et al, 2006; Hodsoll, Viding & Lavie, 2011; Junhong et al, 2013; López-Martin et al, 2013; Müller et al, 2008; Schimmack & Derryberry, 2005; Syrjänen & Wiens, 2013). Two studies showed greater exogenous attention to positive stimuli, and not to negative stimuli, than to neutral stimuli (Aquino & Arnell, 2007; Feng, Wang, Wang, Gu, & Luo, 2012), and in both cases, positive stimuli were of sexual content (the remaining two experiments—Eimer, Holmes & McGlone, 2003; Pessoa et al, 2002—are among those not showing any differential effect of emotional distractors with respect to neutral).…”
Section: Exogenous Attention To Emotional Stimuli: Main Findings and mentioning
confidence: 99%
“…3: 95.67; Exp. 4: 94 %Faces3: Neutral, Negative, Positive (taking the 5 experiments as a whole)Center at 2.86BehaviorYes, BehaviorNeg & PosHuang et al 2011 Exp. 1: 11/12 (18–27).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that capture only occurs in low perceptual load conditions (14,15). Functional MRI (fMRI) has shown that the amygdala response to affective stimuli is modulated by task demands (16,17).…”
mentioning
confidence: 99%